STRATEGI PROMOSI MEDIA BETANG.TV DALAM MENARIK MINAT MASYARAKAT KALIMANTAN TENGAH LEWAT INSTAGRAM - Srie Rosmilawati; Annisa Rizki Ananda; Indah Tri Handayani; Rahmad Taufik (Universitas Muhammadiyah Gresik, 2022)
This research raises the issue of how the development of the Betang.TV company during its establishment, the purpose of this research is of course to find out about the strengths, weaknesses, opportunities and threats of the Betang.TV company. Seeing the mass media market in Central Kalimantan, which is becoming a competitive arena for capturing the market, or at least creating a good image, known to the public as Betang. television target market. From seeing these problems, a promotional strategy was made to introduce this company to the public, not only introducing it, but also being able to reap profits through the strategy used, namely Instagram content by beautifying the Instagram feed (Main Page). From the strategy made, it is hoped that it will produce results for this company. The research method used starts from the data collection process carried out by field observations at the cyber mass media company (Local) PT. Betang.TV Multi Talent, Interview, Review of office location. Researchers analyzed digital data (Website and Social media) and analyzed licensing files. The result of this research is the promotion strategy of Betang.TV, first approach with other media and then ask for exposure from that media. Second, carry out direct promotion by word of mouth and improve the governance of social media settings. Third, branding Instagram Betang TV social media.